Perfil farmacocinético de la gentamicina en cabras en lactación - Esmoris, S. (2020)
The objective of the present study was to describe the pharmacokinetic profile and milk concentrations of gentamicin administered by intravenous, intramuscular and subcutaneous routes in lactating goats. Six healthy lactating goats in their second lactation (40 days postpartum) received a single intravenous, intramuscular and subcutaneous administration of gentamicin at a dosage of 6.6 mg/kg. A 2x2x2 cross over design was employed, the wash out period was 10 days. Blood and milk samples were collected at predetermined time and drug concentrations were determined by microbiological assay. Plasma pharmacokinetic parameters were calculated using compartimental analysis. The pharmacokinetic profile was similar regardless of the route of administration. No differences were detected in the pharmacokinetic parameters. Gentamicin concentrations were no detected in milk. Our results suggest that the pharmacokinetic behavior of gentamicin administered at dose of 6.6 mg/kg to lactating goats would be similar regardless of the route of administration and could be successfully used for the treatment of infections caused by sensitive microorganisms with MIC equal or less than 3.8 or 2.6 µg/mL after sc or im administration, respectively.